Evaluating the desirability of energy inequality mitigation strategies within underserved communities in sub-Saharan Africa - Desmond Eseoghene Ighravwe; Oludolapo Akanni Olanrewaju (Discover Sustainability)
Abstract Due to inequality, millions of people in sub-Saharan Africa lack access to reliable and affordable energy. Attempts to address this challenge have led to the application of different approaches to energy management, such as non-linear modeling techniques. While these approaches have been used to generate information about technical requirements for solving energy inequality, limited information existscresocio-economic information about energy inequality. This research, therefore, uses a multi-criteria decision-making (MCDM) framework to address energy inequality in sub-Saharan Africa. The framework contains a fuzzy analytical hierarchical process (FAHP) for determining criteria importance and VIKOR (VIseKriterijumska Optimizacija i Kompromisno Resenje) for emerging socio-economic criteria and mitigation strategies for energy inequality. Also, the framework contains nine socio-economic criteria and ten mitigation strategies. A sub-urban community was used to evaluate the framework performance. This study compared the VIKOR method performance with a fuzzy PROMETHEE (reference Ranking Organization METHod for Enrichment Evaluation) and a fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The results from the FAHP method showed that environmental sustainability was the fundamental criterion for evaluating mitigation strategies for energy inequality. On the other hand, the results from the VIKOR method indicated that decentralized renewable energy solutions were the most suitable strategy for addressing energy inequality. According to the TOPSIS method results, cross-subsidization models was the best strategy for addressing energy inequality. Based on Spareman's correlation results for VIKOR and TOPSIS methods, it was observed that a significant association between these methods. On the other hand, there was no significant correlation between the VIKOR and PROMETHEEE results. The aggregation of the VIKOR, PROMETHEE, and TOPSIS results show that decentralized renewable energy solution was the best strategy for addressing energy inequality for the case study. The research findings will guide stakeholders, especially investors, on the best action for investment initiatives in sub-Saharan Africa.